The Effect of Buprenorphine on Methamphetamine Cravings. Issue 6 (December 2015) - Salehi, Mehrdad; Emadossadat, Alireza; Kheirabadi, Gholam Reza; Maracy, Mohammad Reza; Sharbafchi, Mohammad Reza
Abstract : Background: Methamphetamine (METH) abuse and dependence present a major global problem. We investigated the efficacy of adding buprenorphine in reducing METH cravings during treatment with the Matrix program. Methods: This was a randomized, double-blind, controlled clinical trial of 40 men between the age of 18 and 40 years who were referred to the addiction treatment center at Noor Hospital from December 2012 to September 2013. All of the selected subjects participated in the Matrix program and were randomly assigned into 2 groups and given either buprenorphine or a placebo. A 4-month intervention program with buprenorphine or a placebo was arranged for each group. Demographic variables of the 2 groups, descriptive indices from the cocaine craving questionnaire-brief (CCQ-Brief), the ratio of urine tests positive for METH, and the frequency of drug complications were regularly evaluated in both groups every 2 weeks and, if not possible, by the third or fourth week. All analyses were performed by SPSS20 using analysis of covariance, χ 2, and t tests. Results: The average of indices from the cocaine craving questionnaire-brief score, except the 2 initial measurements, was significantly lower in the intervention group in all measurements ( P < 0.05). Apart from weeks 3 and 28, the ratio of positive tests was significantly different in all measurements in both groups ( P < 0.05). Conclusions: Buprenorphine augmentation, in comparison with the placebo, significantly reduced the craving to use METH during treatment with the Matrix program.